The Computerized Adaptable Test Battery (BMT-i) for Rapid Assessment of Children's Academic Skills and Cognitive Functions: A Validation Study - Billard, Catherine; Thiébaut, Eric; Gassama, Sahawanatou; Touzin, Monique; Thalabard, Jean-Christophe; Mirassou, Anne; Munnich, Arnold (Frontiers in Pediatrics, 2021)
Learning disabilities in children are a major public health concern around the world, having a prevalence of 8%. At the national level, they are collectively very costly to the governments and raise the issue of appropriate means of screening. Unfortunately, validated tools for preliminary appraisal of learning and cognitive functioning for struggling children are presently restricted to specific age ranges and cognition domains. The purpose of this study was to validate a first line battery for assessment of academic skills and cognitive functions. Materials and Methods: The computerized Adaptable Test Battery, or BMT-i, includes a panel of tests for the first-line assessment of children’s academic skills and cognitive functions. The battery explores skills for the relevant age group in academic skill sets (written language and mathematical cognition) and cognitive domains (verbal, nonverbal, and attentional/executive functions). The authors relied on the results of the tests in a sample of 1,074 Francophone children representative of the mainland French school-age population (ages 4 to 13, in 39 classrooms from 12 French schools). Results: The psychometric characteristics of the empirical data obtained showed acceptable to good test homogeneity, internal consistency (Cronbach’s alpha: >0.70), test–retest reliability (intraclass correlation coefficients ≈ 0.80), and consistency with reference test batteries (correlation coefficient r from 0.44 to 0.96) Conclusion: The BMT-i was validated in a large sample of children in mainstream schools. This validation paves the way for its use in first-line screening of learning disabilities among children with complaints, whether their learning difficulties have been flagged by their parents or by their teachers. Contribution to the Field: Professionals still lack validated tools for preliminary appraisal of cognitive functioning for struggling children. We validated the BMT-i battery among a large representative sample of French children. BMT-i showed acceptable psychometric characteristics and could offer a preliminary appraisal of cognitive functioning for struggling children, to subsequently refer them for appropriate specialized assessments.. Today learning disabilities are not universally recognized, and getting help for them is a complex and often costly process not uniformly covered by the health care system. The BMT-i may make this process more accessible and affordable.